The Influence of Sales Growth and Capital Intensity on Tax Aggressiveness - Syahrani, Andinna Putri Aditya; Fathoni, Muchamad Irham (International Journal of Science and Society, 2025)
This research scrutinizes the behavior of tax aggressiveness exhibited by manufacturing companies listed on the IDX over a five-year period (2016-2020), by using two independent variables as a primary factors sales growth and capital intensity and using Effective Tax Rate (ETR) as the measurement. While previous studies offer conflicting evidence, this paper provides clarity by employing robust empirical analysis. Findings reveal that capital intensity significantly and positively impacts tax aggressiveness, as firms utilize asset depreciation to reduce taxable income. Conversely, sales growth shows no significant effect on tax aggressiveness, suggesting that revenue fluctuations do not necessarily correlate with strategic tax planning. These results underscore the nuanced nature of corporate tax behavior and offer insights for investors, policymakers, and academics to better understand and regulate tax optimization practices. The study contributes to the broader discourse on balancing profit maximization and tax compliance in the corporate sector.